2014
DOI: 10.1111/jpi.12198
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin promotes hepatic differentiation of human dental pulp stem cells: clinical implications for the prevention of liver fibrosis

Abstract: Melatonin's effect on hepatic differentiation of stem cells remains unclear. The aim of this study was to investigate the action of melatonin on hepatic differentiation as well as its related signaling pathways of human dental pulp stem cells (hDPSCs) and to examine the therapeutic effects of a combination of melatonin and hDPSC transplantation on carbon tetrachloride (CCl4 )-induced liver fibrosis in mice. In vitro hepatic differentiation was assessed by periodic acid-Schiff (PAS) staining and mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 51 publications
(82 reference statements)
2
57
0
1
Order By: Relevance
“…Moreover, treatment with melatonin greatly decreased the MDA level and improved GSH-Px activity in the liver [149]. Additionally, a combination of melatonin and human dental pulp stem cells transplantation (hDPSCs) were better at suppressing liver fibrosis and restoring ALT, AST, and ammonia levels in the group of CCl 4 -injured mice than treatment with melatonin or hDPSCs alone [150]. …”
Section: Protective Effects Of Melatonin On Liver Fibrosismentioning
confidence: 99%
“…Moreover, treatment with melatonin greatly decreased the MDA level and improved GSH-Px activity in the liver [149]. Additionally, a combination of melatonin and human dental pulp stem cells transplantation (hDPSCs) were better at suppressing liver fibrosis and restoring ALT, AST, and ammonia levels in the group of CCl 4 -injured mice than treatment with melatonin or hDPSCs alone [150]. …”
Section: Protective Effects Of Melatonin On Liver Fibrosismentioning
confidence: 99%
“…Melatonin has been known as a pleiotropic molecule. It is a potent free radical scavenger and antioxidant , and it also regulates cell proliferation and differentiation . Both melatonin membrane receptors 1 (MT1) and 2 (MT2) are G protein‐coupled receptors and regulate the activation of adenylate cyclase (AC) and phospholipase C (PLC) .…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, a recent study tested the benefits of this treatment and melatonin (5 mg/kg i.p. twice a week) against liver cirrhosis (Cho et al 2015). The authors observed a dose-and time-dependent relationship between melatonin and hepatic markers such as Alb, cytokeratin-18 (Ck18), CCAAT box enhancer-binding protein α (C/Ebpα), and hepatic nuclear factor-1α (Hnf1α).…”
Section: Liver Transplantationmentioning
confidence: 93%